A Comparative Analysis of Reliable and Congestion-Aware Transport Layer Protocols for Wireless Sensor Networks. (30th December 2012) - Sharma, Bhisham; Aseri, Trilok C.
Abstract : Design and implementation of wireless sensor Networks have gathered increased attention in recent years due to vast potential of sensor networks consisting of spatially distributed devices (motes) to cooperatively monitor physical or environmental conditions at different locations. Wireless sensor networks are built upon low cost nodes with limited battery (power), CPU clock (processing capacity), and memory modules (storage). Transport layer protocols applied to wireless sensor networks can handle the communications between the sink node and sensor nodes in upstream (sensor-to-sink) or downstream (sink-to-sensor) direction. In this paper, we present a comparative analysis of reliable and congestion aware transport layer protocols for wireless sensor networks and number of open issues that have to be carefully realized to make use of the wireless sensor networks more efficiently and to enhance their performance. We first list the characteristics of transport layer protocols. We then provide a summary of reliable and congestion aware transport layer protocols with their respective pros and cons and comparison of different protocols based on reliability, congestion control, and energy efficiency. Finally, we point out open research issues of transport layer protocols for wireless sensor networks, which need further attention to overcome the earlier mentioned challenges.